Knowledge and Attitude of Selected Women Beneficiaries about Janani Suraksha Yojana in Samastipur Districts of Bihar - Kumari, Ruby; Kumari, Seema; Prakash, Satya (Asian Pacific Journal of Health Sciences, 2020)
Introduction: The Janani Suraksha Yojana (JSY) is a 100% centrally sponsored scheme launched by the Honorable Prime Minister of our country on April 12, 2005, for reducing maternal and neonatal mortality. JSY integrates cash assistance with antenatal care during the pregnancy period, institutional care during delivery and immediate postpartum period in a health center by establishing systems of coordinated care by the field-level health workers. Reproductive health is a crucial part of general health and a central feature of human development. More than three-quarters of the population of our country live in rural areas lack of knowledge due to maternal and neonatal mortality and morbidity continue to be high despite the existence of national programs for improving maternal and child health in India. JSY provided antenatal and postnatal services an important one being non-utilization or under-utilization of maternal health-care services, especially among the rural poor and urban slum population due to either lack of knowledge or access to health-care services very difficult. The quality of care is more important than the quantity. Pregnancy requires specialized care, generally agreed to be a preventive activity. The concept of healthy mother and healthy baby is an important aspect of maternal and child health. Material and Methods: For this study, we used a questionnaire to collect primary data; secondary data were also used. For the primary data selection, I first came to know about life with selected benefits, then with the help of questioning, I went directly face to face door to door and questioned him, and he gave me an answer an own language. For secondary data, I read a lot of research papers related to this topic and some books, government report, journal abstract, or thesis took many help. This study was conducted in Samastipur district of Bihar. For this purpose, 60 respondents were purposively selected, who were registered in JSY. Results: The finding of the study showed that about 35% have a high level of knowledge about JSY scheme, 43.34% of beneficiaries having a high level of knowledge about cash assistance given under this scheme. Conclusion: About 41.7% of respondents have knowledge about Accredited Social Health Activists workers and 63.3% of respondents have knowledge about the registration timing under the scheme. Followed by out of 60 respondents, 48.34% have overall knowledge regarding JSY services. About 66.6% of beneficiaries have favorable attitude followed by 22.6% beneficiaries having most favorable attitude and only 11.6% of women beneficiaries having the least favorable attitude about JSY scheme.